2003
DOI: 10.1029/2002jb001778
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic earthquake location in complex three‐dimensional velocity models: Application to Switzerland

Abstract: [1] We present a new approach to determine precise and reliable hypocenter locations in the tectonically complex region of Switzerland. A three-dimensional (3-D) P wave velocity model to be used for earthquake relocation is obtained by simultaneously inverting arrival times of local earthquakes for hypocenter locations and 3-D P wave velocity structure. A 3-D P wave velocity model derived from controlled source seismology (CSS) is used as an initial reference model. The final 3-D model thus combines all availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(179 citation statements)
references
References 32 publications
10
168
0
1
Order By: Relevance
“…Stronger peaks will occur at the appropriate depth when contributions from reflected arrivals are correlated. Husen et al (2003) provide the rule of thumb that resolution of the event depth requires at least one station within a distance equal to 1.5 times the source focal depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stronger peaks will occur at the appropriate depth when contributions from reflected arrivals are correlated. Husen et al (2003) provide the rule of thumb that resolution of the event depth requires at least one station within a distance equal to 1.5 times the source focal depth.…”
Section: Discussionmentioning
confidence: 99%
“…Global search algorithms have made it computationally practical to use probabilistic earthquake location and maintain a complete description of the uncertainties contributing to the solution (Lomax, 2000;Husen et al, 2003). These methods, however, are not well suited to real-time applications, because, in general, they do not deal with the association problem and hence are sensitive to interference by other earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…This layer is poorly constrained, with few ray paths, and will couple strongly with the station corrections. Husen et al, (2003) state that "station delays are only meaningful if more than 10 observations per station exist", such corrections are marked in white in the figure and are not interpreted. Otherwise, the corrections seem reasonable with positive corrections in the Midland Valley and around the Solway Firth/Vale of Eden, indicating that the near surface seismic velocity close to these stations is lower than average for that part of the model.…”
Section: Minimum 1-d Velocity Modelmentioning
confidence: 99%
“…We choose this particular set of models since T3 has the roughest topography and, therefore, the largest scattering potential. Following available studies for the alpine region in Switzerland (Husen et al 2003;Steimen et al 2003;Roten et al 2008), we adopt the 1D velocity model shown in Fig. 2.…”
Section: T O P O G R a P H Y A N D 3 -D V E L O C I T Y M O D E L Smentioning
confidence: 99%